2017
DOI: 10.1021/acsami.6b13362
|View full text |Cite
|
Sign up to set email alerts
|

Solution-Processed Nb:SnO2 Electron Transport Layer for Efficient Planar Perovskite Solar Cells

Abstract: Electron transport layer (ETL), facilitating charge carrier separation and electron extraction, is a key component in planar perovskite solar cells (PSCs). We developed an effective ETL using low-temperature solution-processed Nb-doped SnO (Nb:SnO). Compared to the pristine SnO, the power conversion efficiency of PSCs based on Nb:SnO ETL is raised to 17.57% from 15.13%. The splendid performance is attributed to the excellent optical and electronic properties of the Nb:SnO material, such as smooth surface, high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
198
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(204 citation statements)
references
References 67 publications
6
198
0
Order By: Relevance
“…Concerning materials, TiO 2 has been widely adopted in such duallayer structured ETL for M-PSCs so far [8,[12][13][14][15]. Actually, many attempts have been performed in order to make ETL kinetically more favorable, e.g., surface modifications, nanostructure tailoring, and the utilizations of alternative materials with better optoelectronic properties [16][17][18][19][20][21][22][23]. Compared with TiO 2 , SnO 2 is chemically stable as well and, more importantly, its charge mobility is almost two orders of magnitude higher than that of TiO 2 [11,24].…”
Section: Introductionmentioning
confidence: 99%
“…Concerning materials, TiO 2 has been widely adopted in such duallayer structured ETL for M-PSCs so far [8,[12][13][14][15]. Actually, many attempts have been performed in order to make ETL kinetically more favorable, e.g., surface modifications, nanostructure tailoring, and the utilizations of alternative materials with better optoelectronic properties [16][17][18][19][20][21][22][23]. Compared with TiO 2 , SnO 2 is chemically stable as well and, more importantly, its charge mobility is almost two orders of magnitude higher than that of TiO 2 [11,24].…”
Section: Introductionmentioning
confidence: 99%
“…2b, the peaks around 26.5°, 34.0°and 51.9°were corresponding to the (110), (101) and (211) diffraction planes of tetragonal rutile SnO 2 (JCPDS 21-1250), respectively [38]. With the doping of Nb 5+ , the peak slightly shifted to lower 2θ values, which indicated the lattice shrinkage due to the slightly larger radius of Nb 5+ compared to Sn 4+ [32]. Subsequently, the optical transmittance of the pristine SnO 2 and doped SnO 2 films was carefully studied since the light transmittance of the ETL could directly influence the light absorption of the top perovskite light absorber.…”
Section: Resultsmentioning
confidence: 96%
“…Herein, we for the first time doped Nb 5+ into the low-temperature SnO 2 sol-gel route (under 100°C) due to the close ionic radius of Nb 5+ to Sn 4+ , to tailor the electrical property of SnO 2 layers and the band alignment between SnO 2 and the normally used mixed perovskites for further improvement in charge injection and transport. It was previously reported that Nb-doping could be realized by adding niobium ethoxide or niobium chloride in the SnCl 2 ·2H 2 O solution, followed by a high annealing temperature (~190°C) for the crystallization of SnO 2 [32,33]. In our work, Nb-doped SnO 2 was crystallized with the refluxing (at 78°C) and aging process (at 40°C), and the temperature of the whole fabrication process was under 100°C, which would reduce the fabrication consumption and show potential application in the flexible devices.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the excitons, generated in perovskite layer, separate at the interface and diffuse directly to the ETL. Therefore, the ETL in N-I-P type planar structure is essential for the crystallization and morphology of perovskite films [15,16] and used to extract electrons [17][18][19]. Until now, TiO 2 is the most widely used ETL in perovskite solar cells [20][21][22]; however, ZnO has a higher carrier mobility, conductivity and a similar energy band profile with TiO 2 , ensuring a faster electron transport.…”
Section: Introductionmentioning
confidence: 99%